Domestic violence and its effects on education: a proposal or challenge for a culture of peace (Research, Society and Development, 2020)
The article aimed to analyze the intrafamilial violence and the reflexes in the education, a proposal or a challenge for the culture of peace. Thus, it was proposed to build literature review, using bibliographic research so that the data obtained were analyzed under the qualitative explanatory paradigm. The results made it possible to characterize violence against women, the forms of manifestation of this violence, the role of the Maria da Penha Law in the practice of combating gender violence and some public policies to combat it. It can be concluded that care for victims of intrafamilial violence requires specialized professionals, suitable places for these victims to feel safe and at peace with themselves to make their reports. In the context of education, all victims of facts of intrafamily violence need to be advised regarding the report of the perpetrator of violent acts, so that the state becomes aware of and guarantees them protection and social welfare to continue to live despite their suffering, from the physical and psychological consequences to the victims and with the accompaniment of the State assistance apparatus.